Genomics of Tumor Origin and Characteristics for Adenocarcinoma and Malignant Pleural Mesothelioma: A Case Report - Usuda, Katsuo; Niida, Yo; Ishikawa, Masahito; Iwai, Shun; Yamagata, Aika; Iijima, Yoshihito; Motono, Nozomu; Yamada, Sohsuke; Uramoto, Hidetaka (Frontiers in Oncology, 2022)
A female underwent a right middle lobectomy for a pulmonary adenocarcinoma (AD). She eventually died of a right malignant pleural mesothelioma (MPM) (sarcomatoid type) 4 years and 7 months after the removal of the AD even though she did not have any history of asbestos, smoking or radiation exposure. Her chest CT revealed multiple pulmonary nodules, and bilateral pleural effusion with a right pleural tumor directly invaded into the abdominal cavity. The genomics of tumor origin and characteristics were examined for the AD and the MPM. As a result, 50 somatic variants were detected in the AD, and 29 somatic variants were detected in the MPM. The variants which were common in both the AD and the MPM were not present, which suggested that the AD and the MPM had occurred independently in different origins. The MPM had two driver oncogenes of TP53 and EP300, but the AD did not. Two driver oncogenes of TP53 and EP300 were hypothesized to make the MPM aggressive. The speed at which the MPM progressed without the patient having a history of asbestos, smoking, or radiation exposure was alarming.